THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION IN BANK SINARMAS MEDAN BRANCH - Billie Ewaldo Thonora; Alfonsius Alfonsius (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
Product quality and service quality play an essential role in every business, as they will influence customer satisfaction. Banking industries are one of many industries that keep maintaining customer satisfaction to have competitive advantages over competitors. This study aims to evaluate and measure the effect of product quality and service quality on customer satisfaction at Bank Sinarmas Medan Branch simultaneously and partially. The sample in this study was 178 customers of Bank Sinarmas Medan Branch. The data was collected by using a questionnaire. The data analysis technique used is multiple linear regression analysis. The research results show a simultaneous influence of product quality and service quality on customer satisfaction in Bank Sinarmas Medan Branch. Product quality influences customer satisfaction at Bank Sinarmas Medan Branch, and service quality influences customer satisfaction at Bank Sinarmas Medan Branch.